PENERAPAN MODEL KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN KEAKTIFAN PEMBELAJARAN PPKn SISWA KELAS VII SMP - Raudatul Jannah; Okianna Okianna; Bambang Budi Utomo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe results of preliminary observations showed that student engagement in the learning is still low with an average of 35.83%. This study aimed to collect data and precise information on implementing the Jigsaw technique to improve students' engagement in civic education instruction. The research method used is descriptive in the form of collaborative classroom action research. The subjects studied were thirty VII grade students of SMP Kartika XVII-1 Sungai Raya. Data collection techniques used were direct observation techniques, with observation sheets of teacher ability in preparation and implementing instructions, and student activity observation sheets as the data collection tools. This research was conducted in 3 cycles with the results collected as follows, the ability of teachers to plan instructions from the cycle I obtained an averagescore of 3.10 with a good category, an average score of 3.47 with a good category in cycle II, and an average score of 3.94 with an excellent category in cycle III. The ability of teachers to implement instructions from the cycle I obtained an average score of 3.04 with a good category, an average score of 3.46 with a good category in cycle II, and an average score of 3.95 with an excellent category in cycle III. Student engagement in the initial observations with an average value of 35.83% was obtained with a very low category; the cycle I obtained an average value of 62.08% with a sufficient category; cycle II obtained an average value of 76.25% with a good category; cycle III obtained an average value of 85.00% with a very high category. Grounded on the findings, it can be concluded that there is an improvement in each cycle. Therefore, the jigsaw technique can increase class VII Kartika XVII-1 Sungai Raya students engagements in Civic Education instruction.Keywords: Civic Education, Cooperative Learning Model Jigsaw Technique, Student Engagement.